Common fixed points for generalized ψ -contractions in weak non-archimedean fuzzy metric spaces - Suthep Suantai (2019)
© 2019, Universitat Politecnica de Valencia. All rights reserved. Fixed point theory in fuzzy metric spaces plays very important role in theory of nonlinear problems in applied science. In this paper, we prove an existence result of common fixed point of four nonlinear mappings satisfying a new type of contractive condition in a generalized fuzzy metric space, called weak non-Archimedean fuzzy metric space. Our main results can be applied to solve the existence of solutions of non- linear equations in fuzzy metric spaces. Some examples supporting our main theorem are also given. Our results improve and generalize some recent results contained in Vetro (2011) [16] to generalized contractive conditions under some suitable conditions and many known results in the literature.